A SIMPLE METHOD OF REPRESENTING DIEL VARIATIONS OF A PARAMETER IN THE FORM OF DIURNAL, SEMIDIURNAL AND QUARTERDIURNAL WAVES - Murty, A V S (Indian Journal of Fisheries, 2011)
The observations on a fluctuating parameter over a diel period of 24 hare transformed into three cascade waves, namely the diurnal wave, semidiurnalwave and quarterdiurnal wave, which oscillate over the steady (mean) value ofthe parameter. Such a transformation of the varying parameter is effected by avery simple analytical method based on the choice of sixteen ordinates of theparameter equidistantly placed in the diel period.